Management of juvenile ossifying fibroma: insights from three cases and a review of literature - Sharma, Sahil; Wadhera, Raman; Kumar, Bhavesh; Anand, Anshika; Saini, Nishant; Kush, Archana; Rani, Preeti (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Juvenile ossifying fibroma (JOF) is a rare, benign fibro-osseous neoplasm exhibiting locally aggressive behaviour predominantly localized within the craniofacial bones. This distinct entity is distinguished from ossifying fibroma (OF) by its earlier age of onset and an increased propensity for recurrence. A comprehensive review of existing literature, supplemented by a case series, is presented to elucidate the clinical, radiological, and histopathological characteristics of JOF. Diagnostic challenges associated with JOF are often encountered due to its variable presentation and potential overlap with other fibro-osseous lesions. Treatment is by surgical resection, with a focus on obtaining total excision to reduce the chance of recurrence. Long-term follow-up is crucial for early detection of recurrence. This combined literature review and case series presentation aims to improve knowledge of JOF, enabling more accurate diagnosis and effective therapy.